EFFECTIVENESS OF CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) COUNSELING BY THE HEALTH OFFICE WITH STUDENT ATTITUDES - Astuti, Linda; Tika, Yori Manis; Intan, Dyah Noor; Susanto, Prio; Indriani, Heni (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
This research is about the effectiveness of counseling on clean and healthy living behavior (PHBS) by the Health Service with student attitudes. This research aims to determine the effectiveness of counseling on clean and healthy living behavior (PHBS) by the Health Service on student attitudes. Data collection techniques through observation and distribution of questionnaires and secondary data through literature study. The population in this study were students at SMPN 20 Bengkulu City. The sample in this study was taken using a census sampling technique from the population, so the total sample size was 75 people. Data analysis was carried out using Product Moment correlation and f-test. The results of the research show that there is a relationship between the effectiveness of counseling on clean and healthy living behavior (PHBS) by the Health Service and student attitudes. This is proven by the calculated results being greater than the r table, namely 1.225 > 0.227. The results of testing the significance of the correlation coefficient using the f-test, the results of the f-test calculation are greater than the f-table, namely 208,825 > 2.80. Thus, the hypothesis proposed in this research is accepted, namely that the Health Service's Clean and Healthy Living Behavior Extension is effective in changing students' attitudes..